Penyusunan Instrumen Keterampilan Proses Sains Berbasis Inkuiri Kontekstual pada Perkuliahan Mikrobiologi - Hasruddin, Hasruddin; Harahap, Fauziyah; Mahmud, Mahmud (Universitas Sebelas Maret, 2018)
The study aims to determine the level of feasibility and effectiveness of science process skill instruments in contextual inquiry at microbiology courses in Biology Education Program of Universitas Negeri Medan (Unimed). The r development esearchthrough the stages Analysis, Define, Development, Implementation, and Evaluation (ADDIE). The draft of science process skill instrument is validated by 2 microbiology material experts, 2 design learning experts, 2 evaluation experts, and 2 linguists. Individual trials were conducted on 3 students of biology education, small group trials were conducted on 9 students, and large group trials were conducted to 21 biology education students who were enrolled in microbiology courses. Data were analyzed using percentage technique and presented in frequency table form. The results of the study found that the development process skill instruments categorized as